Online teaching and learning during COVID-19: flexible harmonies in Higher Education (Comparative & International Education Series, 2021)
As COVID‐19 impacts and transforms the world, Higher Education ‘press on with business as usual’ moving to online education. While online teaching is not new, this chapter builds on our previous study See, Listen and Share: Exploring Intercultural Music Education in a Transnational Experience that employed online teaching across three universities. Using Technological Pedagogical Content Knowledge as a guide teaching diverse cohorts of students (Australia and Spain), we employ narrative enquiry methodology to reflect in and on our practice during the pandemic. Our findings highlight current challenges, dilemmas and opportunities we encountered in relation to student learning and working from home using a range of interactive multimedia tools to present our music classes. We contend that staying connected and sharing about intercultural practice contributes positively to wellbeing, building our resilience as we navigate the remainder of the year and beyond with universities facing significant transformational changes.